Application of Different Aqueous Ultrasound-assisted Extraction Process Parameters on the Quality of Pandan (Pandanus amaryllifolius Roxb) Leaves Extract (Journal of Biochemistry, Microbiology and Biotechnology, 2024)
Pandan of Pandanaceae family, known for its aromatic foliage, vibrant green color, and rich in bioactive compounds, requires green extraction technology to stabilise compounds. Hence, this study aims to optimise process parameters of aqueous ultrasound-assisted extraction (UAE) on the color, yield, and antioxidant content of pandan extract using the Response Surface Method (RSM), and compare the volatile compounds present in optimised ultrasonicated pandan extract with macerated extract (control). The analysis includes DPPH and FRAP assays, total phenolic content (TPC), color, and yield. Optimally validated parameters (R2 ≥ 0.90, p-value lack-of-fit ≥ 0.05) were: 80°C extraction temperature, 90 min ultrasonic time, 2.60 % of solid in 20 mL distilled water yielded promising antioxidant activities: 277.64 mg/g AAE, 19.90 mg/g GAE, and 1.48 g/g AAE for DPPH, TPC, and FRAP assays, respectively). UAE technique has significantly (p
Keywords: Aqueous Extract; Bioactive Compounds; 3-methyl-2(5H)-furanone; Volatile Analysis; Pandanus amaryllifolius Roxb